FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH TERHADAP LAYANAN MOBILE BANKING DI BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU (KCP) BOGOR DRAMAGA - Destriana Maulani; Tubagus Rifqy Thantawi; Miftakhul Anwar (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This study aims to determine the factors that influence customer interest in mobile banking services offered by Bank Syariah Indonesia KCP Bogor Dramaga. In this study using quantitative methods, by collecting data using questionnaires and google forms with Likert scale measurements, with non-probabilistic sampling techniques, and the method used was purposive sampling. The results of this study are; 1) the ease of use factor (X1) has a positive effect at a significance level of 5% partially on customer interest; 2) the safety factor (X2) has no effect on the 5% significance level partially on customer interest; 3) the time efficiency factor (X3) has a positive effect at a significance level of 5% partially on customer interest; 4) the ease of use factor (X1), the safety factor (X2), and the time efficiency factor (X3) have a positive effect at a significance level of 5% simultaneously on customer interest. With this research, it can be concluded that the factors of ease of use and time efficiency affect customer interest in using mobile banking services.